A General Modeling Approach for Shock Absorbers: 2 DoF MR Damper Case Study - Lozoya-Santos, Jorge de-J.; Tudon-Martinez, Juan C.; Morales-Menendez, Ruben; Sename, Olivier; Spaggiari, Andrea; Ramírez-Mendoza, Ricardo (Frontiers in Materials, 2021)
A methodology is proposed to design a mathematical model for shock absorbers; the proposal is guided by characteristic diagrams of the shock absorbers. These characteristic diagrams (Force- Displacement, Velocity-Acceleration) are easily constructed from experimental data generated by standard tests. By analyzing the diagrams at different frequencies of interest, they can be classified into one of seven patterns, to guide the design of a model. Finally, the identification of the mathematical model can be obtained using conventional algorithms. This methodology has generated highly non-linear models for 2 degrees of freedom magneto-rheological dampers with high precision (2 - 10 % errors).